Acyl‐homoserine lactone acylase from Ralstonia strain XJ12B represents a novel and potent class of quorum‐quenching enzymes - Lin, Yi‐Han; Xu, Jin‐Ling; Hu, Jiangyong; Wang, Lian‐Hui; Ong, Say Leong; Leadbetter, Jared Renton; Zhang, Lian‐Hui (Molecular microbiology, 2003)
Summary N ‐acylhomoserine lactones (AHLs) are used as signal molecules by many quorum‐sensing Proteobacteria. Diverse plant and animal pathogens use AHLs to regulate infection and virulence functions. These signals are subject to biological inactivation by AHL‐lactonases and AHL‐acylases. Previously, little was known about the molecular details underlying the latter mechanism. An AHL signal‐inactivating bacterium, identified as a Ralstonia sp., was isolated from a mixed‐species biofilm. The signal inactivation encoding gene from this organism, which we call aiiD , was cloned and successfully expressed in Escherichia coli and inactivated three AHLs tested. The predicted 794‐amino‐acid polypeptide was most similar to the aculeacin A acylase (AAC) from Actinoplanes utahensis and also shared significant similarities with cephalosporin acylases and other N‐terminal (Ntn) hydrolases. However, the most similar homologues of AiiD are deduced proteins of undemonstrated function from available Ralstonia , Deinococcus and Pseudomonas genomes. LC‐MS analyses demonstrated that AiiD hydrolyses the AHL amide, releasing homoserine lactone and the corresponding fatty acid. Expression of AiiD in Pseudomonas aeruginosa PAO1 quenched quorum sensing by this bacterium, decreasing its ability to swarm, produce elastase and pyocyanin and to paralyse nematodes. Thus, AHL‐acylases have fundamental implications and hold biotechnological promise in quenching quorum sensing.